2021
DOI: 10.3390/brainsci11020256
|View full text |Cite
|
Sign up to set email alerts
|

Forefront Users’ Experience Evaluation by Employing Together Virtual Reality and Electroencephalography: A Case Study on Cognitive Effects of Scents

Abstract: Scents have the ability to affect peoples’ mental states and task performance with to different extents. It has been widely demonstrated that the lemon scent, included in most all-purpose cleaners, elicits stimulation and activation, while the lavender scent elicits relaxation and sedative effects. The present study aimed at investigating and fostering a novel approach to evaluate users’ experience with respect to scents’ effects through the joint employment of Virtual Reality and users’ neurophysiological mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…Aromatherapy is a discipline that has been used for millennia as an alternative medicine in different cultures, resulting in effective treatment of some disorders such as insomnia [ 1 ], anxiety [ 2 ], and depression [ 3 ]. In addition to these clinical applications, the effects of fragrances on the human mind and behavior is also of great interest for all those applications related to everyday life, such as cosmetics, personal care, nutrition, comfort, and psychophysical well-being [ 4 , 5 ]. The power of scents has always fascinated scientists, who tried to demonstrate their impact at the human psychophysiological level using the most advanced technologies for biosignal and neuroimaging analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Aromatherapy is a discipline that has been used for millennia as an alternative medicine in different cultures, resulting in effective treatment of some disorders such as insomnia [ 1 ], anxiety [ 2 ], and depression [ 3 ]. In addition to these clinical applications, the effects of fragrances on the human mind and behavior is also of great interest for all those applications related to everyday life, such as cosmetics, personal care, nutrition, comfort, and psychophysical well-being [ 4 , 5 ]. The power of scents has always fascinated scientists, who tried to demonstrate their impact at the human psychophysiological level using the most advanced technologies for biosignal and neuroimaging analyses.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent investigations have shown the potential of multisensory integration in fully immersive VR (fiVR) which would facilitate the formation of spatial presence, generally understood as the sense of “being there”. Such a result is achieved by adding to the user experience auditory elements such as audio-realistic sequences representing so-called “soundscapes” [ 117 , 118 ] and even scents which has been proven to modulate the request of cognitive resources during the processing of informative messages [ 119 ].…”
Section: Resultsmentioning
confidence: 99%
“…Brain metrics, including band power and graph theoretical metrics, were computed from preprocessed data for each trial. Specifically, the short time Fourier transform (STFT) method was used to compute power spectral density (PSD) in five frequency bands power (delta [1][2][3][4], theta [4][5][6][7][8], alpha [8][9][10][11][12], beta [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], and gamma [30][31][32][33][34][35][36][37][38][39][40]). The PSD was then estimated in each frequency band as:…”
Section: Feature Extraction-brain Metricsmentioning
confidence: 99%
“…Other studies demonstrated the efficiency of olfaction in enhancing spatial attention, as part of multisensory strategies for neurorehabilitation [ 14 ]. Recent work further showed the effect of scents on influencing affect in the context of technology acceptance [ 18 ], or enhancing cognitive states such as emotion [ 19 ], selective attention [ 20 ], and cognitive load [ 21 ].…”
Section: Introductionmentioning
confidence: 99%